Jack Ryan : Oath of Office - Book 26 - Cameron, Marc (New York : Berkley, 2019)
Marine officer. CIA analyst. President. Jack Ryan has devoted his life to protecting the United States. What if this time, he cant? When a change of regimes in Iran presents new opportunities for a balance of power in the region, President Jack Ryan becomes a lone Western voice in urging caution in the wake of an international arms dealers rise to power.
Keywords: Ryan, Jack, -- Sr. (Fictitious character) -- Fiction; Ryan, Jack, -- Jr. (Fictitious character) -- Fiction; Intelligence officers -- United States; Fiction; Terrorism -- Prevention; Fiction; Thrillers (Fiction); Suspense fiction